Effect of heat treatment on microstructure and mechanical behaviours of 18Ni-300 maraging steel manufactured by selective laser melting. (December 2019) - Song, Jun; Tang, Qian; Feng, Qixiang; Ma, Shuai; Setchi, Rossitza; Liu, Ying; Han, Quanquan; Fan, Xiaojie; Zhang, Mengxiang
Highlights: The process parameters of 18Ni-300 maraging steel fabricated by SLM were optimised. The effect of various heat treatments on phase transformation and microstructure was discussed. Vertically-built samples exhibited slightly lower tensile strength than those horizontally-built. Abstract: Selective laser melting (SLM) of 18Ni-300 maraging steel is an important research area in view of its numerous applications in the automotive domain. Heat treatment plays a significant role in the microstructure and mechanical behaviour of maraging steels and is a major area of interest. This paper investigated the effect of heat treatment on microstructure and mechanical behaviour of SLM-built 18Ni-300 maraging steel. The experimental results showed that the densest parts with the smallest number of defects were fabricated at optimum laser energy density of 70 J/mm 3 and laser power of 275 W. When the laser power was fixed at 275 W, lower laser energy density resulted in the formation of balling and irregular pores, while higher laser energy density induced spherical pores and microcracks. The as-built samples consisted of cellular and columnar microstructures due to the fast cooling and solidification rates during SLM. However, solution treatment led to changes in the typical microstructure and massive lath martensite phase. The tensile strength and microhardness decreased slightly due to grain growth and residual stress relief upon solution treatment; an opposite effect was observed when the samples were subjected to solution treatment followed by aging at 490 °C for 2 h. With regard to the tensile anisotropy, yield strength and ultimate tensile strength of the horizontally-built samples slightly exceeded those vertically-built. These findings are significant as they allow an informed prediction about the effect of various heat treatments on the microstructure and mechanical behaviour of components manufactured from 18Ni-300 maraging steel using the SLM process.